أثر اللُّغة العربية وآدابها في تشكيل اللهجات العربية المحليّة (Faculty of Education Scientific Journal, 2025)
Language is a social and human phenomenon aimed at interaction between the individual and society. Language is considered one of the most important discoveries of humanity in the history of its human and civilizational journey. Language is the only means of expression among humans, without which the natural human life among members of society would cease to exist. And the Arabic language is not an exception among languages; it undergoes the same processes as other human languages in terms of the functions it performs and carries out within the societal linguistic structure of the nation. But over time, and due to linguistic evolution influenced by historical and geographical factors, parallel languages emerged from the mother language, known as dialects. These local dialects dominated Arab societies, leading to a diglossia between the mother language and the local dialect, and how communities interacted with both. This resulted in a significant gap between society, the mother language, and the dialect dominating the community discourse of the nation. The search here is for the truth of this relationship between the official language of the society and the local dialects, and the extent of their impact on the classical language, whether positively or negatively.
Keywords: Arabic Linguistic; Identity; Dialects; Quraish dialect; Classical; Slang. Mother tongue